Calvin's New Testament commentaries ; vol. 5 - Calvin, John, 1509-1564; Parker, T.H.L.; Torrance, David W.; Torrance, Thomas Forsyth, 1913- (Grand Rapids, MI Eerdmans, 1972)
Contents : v. 5 : The gospel according to St John 11-21 and the first epistle of John. Includes bibliographical references and indexes.
Keywords: Bible. N.T. John XI-XXI -- commentaries; Bible. N.T. Epistles of John, 1st -- commentaries